Sprężyste Fale Giętne w Nieskończonej Rurze przy Przepływie Płynu Nieściśliwego - Bobeszko, A. (Engineering Transactions, 1963)
This paper contains a discussion of several aspects of the propagation problem of flexural e waves in an infinite tube containing flowing incompressible fluid. The equations of motion of the tube are derived assuming variable cross-sectional area and non-steady-state flow. Various bending theories (elementary, Rayleigh and Timoshenko) are used to discuss the form of the dispersion curves. On the grounds of the elementary theory the influence of the type of velocity distribution in the cross section on the value of the critical flow velocity is considered.